Proposed business strategy and development for lookwaxy in order to gain competitive advantage - Kirana Putri, Astari; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2016)
Abstract – Lookwaxy is premium shoe laundry service that has been established since May 2015. As a growing business concept nowadays and big potential market, Lookwaxy should have positive growth whilst their position as first mover in South Tangerang area. However the sales not show a significant growth. The entrance of several established competitors, plenty numbers of conventional laundry service which also offer shoe laundry and the nature of the business which doesn’t need specific capabilities, also moderately costly to imitate threaten the position of Lookwaxy in the market of potential new entrants. In order to compete in the competitive market, Lookwaxy should find and gain their competitive advantage. To gain a competitive advantage, the analysis was needed to describe the strategy and the right business model. In analyzing; qualitative methods used to interview the BOD of Lookwaxy and questionnaire to 156 respondents in South Tangerang, secondary data from books, literatures and other sources from the internet. Formulating strategies started by conduct external and internal assessment using PEST analysis, Porter’s Five Forces, Competitor mapping, Value Chain, and VRIO framework. This assessment will generate SWOT analysis that describes Lookwaxy’s condition. All the information then used to formulate the alternative strategies using TOWS matrix. Porter’s generic model also used to see company current position and proposed strategy. Furthermore, the development of a Business Model Canvas and new business strategy for the company were generated. All the strategy and business development models will be used in the implementation of the plan to assist and provide Lookwaxy solution to solve the problems. The implementation plan involves various things like; enhance service excellence value, adding service specialization in leather shoes service and product, offer delivery service, open new branch or drop off counter, boost event marketing and sales promotion program both in offline and online media (Instagram), as well as increase organizational capabilities in R&D. Keywords: Business Strategy, Business Model Canvass